Destinação dos resíduos químicos de um laboratório de análises clínicas: uma proposta de modelo de gestão - Botton, Salimara Rampelotto (2011)
The discussion about the question of appropriate management of chemical waste has increased in recent years. Thus, this study aimed at analyzing the Chemical Waste Management System used in the Hematology Division health services of the Santa Maria University Hospital Clinical Analysis Laboratory (CAL). From an in loco observation of the chemical waste management conducted by the CAL Department of Hematology, a diagnosis was made based on documental and photographic assessment. This is an exploratory and descriptive study which used an approach both qualitative and quantitative, and is characterized as a case study. It was found that most of the chemical reagents in the composition of the solutions used by the hematological analysis equipments present toxicity and are hazardous to the health of those who manipulate them and to the environment. Thus, this study offered a proposal for the destination and management of the chemical waste generated by the CAL Division of Hematology. It is believed that such a proposal is fundamental to minimize the impacts of the current practices on the environment and human health.